RELATIONS BETWEEN ANTHROPOMETRIC CHARACTERISTICS AND LATENT DIMENSIONS OF STRENGTH IN PERSONS OF ABOVE-AVERAGE MOTOR ABILITIES - Milan Cvetkoviċ; Damjan Jakšiċ; Dejan Orlić (Exercise and Quality of Life)
Mere enrollment on the Faculty of Sport and Physical Education assumes that the population has been selected according to several criteria. One of the most typical criteria is motor development, hence students of sport and physical education might be treated as persons of above-average motor abilities. Test battery of 17 anthropometrical tests and 14 strength tests has been applied on the sample of 149 males, students of the Faculty of Sport and Physical Education in Novi Sad. The purpose of this paper is to determine relations between anthropometrical measures and latent dimensions of strength. Within the latent space of strength, after Promax rotation of major components and based on KG criteria, three strength factors have been isolated: static and repetitive strength, especially that of hands and trunk to a lesser degree, explosive strength of legs, and explosive strength of arms. Finaly, three statistically significant canonical correlations have been isolated. The first is that of explosive strength of arms having negative correlation with all anthropometrical variables, the second is explosive strength of legs which is in negative correlation with subcutaneous fat tissue of upper leg and triceps, but in positive correlation with the measures of longitudinal dimensionality of skeleton, whereas the third is static and repetitive strength of arms (and trunk to a lesser degree) being in negative correlation with body height and leg length.